2014
DOI: 10.1016/j.pain.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

tDCS modulates cortical nociceptive processing but has little to no impact on pain perception

Abstract: Transcranial direct current stimulation (tDCS) effectively modulates cortical excitability. Several studies suggest clinical efficacy in chronic pain syndromes. However, little is known regarding its effects on cortical pain processing. In this double-blind, randomized, cross-over, sham controlled study, we examined the effects of anodal, cathodal, and sham stimulation of the left motor cortex in 16 healthy volunteers using functional imaging during an acute heat pain paradigm as well as pain thresholds, pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 67 publications
(104 reference statements)
5
40
1
Order By: Relevance
“…However, other researchers have also been obtained in which A-tDCS was ineffective in the treatment of chronic pain using the same conditions (Ihle et al, 2014; Nardone et al, 2014) The patient described in this study had stable chronic pain for at least 6 months with a high VAS scores before the stimulation, however, intervention time was not considered during therapy. A proper intervention time, the number of session and the length of stimulus duration should be considered and may be dependent on different states and causes of illness (Ihle et al, 2014). Our results suggest that clinicians should consider personalized treatment in patients with chronic neuropathic pain, pay attention to specific stimulus parameters and disease characteristics.…”
Section: Discussionmentioning
confidence: 71%
“…However, other researchers have also been obtained in which A-tDCS was ineffective in the treatment of chronic pain using the same conditions (Ihle et al, 2014; Nardone et al, 2014) The patient described in this study had stable chronic pain for at least 6 months with a high VAS scores before the stimulation, however, intervention time was not considered during therapy. A proper intervention time, the number of session and the length of stimulus duration should be considered and may be dependent on different states and causes of illness (Ihle et al, 2014). Our results suggest that clinicians should consider personalized treatment in patients with chronic neuropathic pain, pay attention to specific stimulus parameters and disease characteristics.…”
Section: Discussionmentioning
confidence: 71%
“…In other words, we did not manipulate pain sensation but rather the learned association between an a priori neutral cue and pain intensity and tested the effect of tDCS extending beyond the period of stimulation. Similarly to the study of Ihle and colleagues [23], we compared anodal and cathodal stimulation directly and found a significant difference in pain ratings in response to different cues. The conditioning effects (placebo, i.e.…”
Section: Discussionmentioning
confidence: 75%
“…Most of these studies targeted M1 but in the study by Boggio and colleagues they additionally stimulated the left DLPFC with anodal tDCS and reported a similar pain decrease [7]. These results, however, were not fully supported by a more recent study [23], showing non-significant pain reduction in the post- minus pre- M1 stimulation in the anodal tDCS group and no differences in pain ratings between the tDCS groups, albeit with a lower intensity (1mA) and duration (15 minutes) than used in other clinical studies [15,52]. Despite the lack of an analgesic effect, the authors demonstrated differences in BOLD signal within pain-processing regions between the anodal and the cathodal groups.…”
Section: Discussionmentioning
confidence: 99%
“…They found that neither cathodal nor anodal tDCS over the left M1 (1 mA, 15 minutes) significantly changed cortical nociceptive processing as a response to a heat pain paradigm when compared with sham stimulation. Only contrasting the interaction between responses to anodal and cathodal stimulation, It was found a substantial polarity-specific differences of regional brain activation after painful stimulation: anodal stimulation induced a decrease of regional Cerebral Blood Flow (rCBF), whereas cathodal stimulation resulted in an increase of rCBF in the hypothalamus, inferior parietal cortex, inferior parietal lobule, anterior insula, and precentral gyrus contralateral to the stimulation site 38 .…”
Section: Discussionmentioning
confidence: 98%
“…Ihle et al ., 38 , developed a study using functional imaging to explore the underpinnings of the previously suggested antinociceptive effects of tDCS over the motor cortex 38 . They found that neither cathodal nor anodal tDCS over the left M1 (1 mA, 15 minutes) significantly changed cortical nociceptive processing as a response to a heat pain paradigm when compared with sham stimulation.…”
Section: Discussionmentioning
confidence: 99%